Ageing is associated with diminished muscle re‐growth and myogenic precursor cell expansion early after immobility‐induced atrophy in human skeletal muscle. (8th July 2013) - Suetta, C.; Frandsen, U.; Mackey, A. L.; Jensen, L.; Hvid, L. G.; Bayer, M. L.; Petersson, S. J.; Schrøder, H. D.; Andersen, J. L.; Aagaard, P.; Schjerling, P.; Kjaer, M.
Key points Elderly individuals require a prolonged recovery phase in order to return to initial muscle mass levels following short‐term immobilisation. The cellular mechanisms responsible for the attenuated re‐growth and associated molecular signalling processes in ageing human skeletal muscle are not fully understood. The main study finding was the observation of a less marked muscle mass recovery after immobilisation in elderly compared to young individuals that was paralleled by an elevation in myogenic precursor cell content in young individuals only, whereas the elderly failed to demonstrate any change in myogenic precursor cells. No age‐related differences were observed in the expression of major myogenic regulating factors known to promote skeletal muscle hypertrophy or satellite cell proliferation (IGF‐1Ea, MGF, MyoD1, myogenin, HGF gene products). In contrast, the expression of myostatin demonstrated a more pronounced up‐regulation following immobilisation along with an attenuated down‐regulation in response to reloading in older compared to young individuals, which may have contributed to the present lack of satellite cell proliferation in ageing muscle. Abstract Recovery of skeletal muscle mass from immobilisation‐induced atrophy is faster in young than older individuals, yet the cellular mechanisms remain unknown. We examined the cellular and molecular regulation of muscle recovery in young and older human subjects subsequent to 2 weeks of immobility‐induced muscle atrophy. Retraining consisted of 4 weeks of supervised resistive exercise in 9 older (OM: mean age) 67.3, range 61–74 yrs) and 11 young (YM: mean age 24.4, range 21–30 yrs) males. Measures of myofibre area (MFA), Pax7‐positive satellite cells (SCs) associated with type I and type II muscle fibres, as well as gene expression analysis of key growth and transcription factors associated with local skeletal muscle milieu, were performed after 2 weeks immobility (Imm) and following 3 days (+3d) and 4 weeks (+4wks) of retraining. OM demonstrated no detectable gains in MFA (vastus lateralis muscle) and no increases in number of Pax7‐positive SCs following 4wks retraining, whereas YM increased their MFA (P < 0.05), number of Pax7‐positive cells, and had more Pax7‐positive cells per type II fibre than OM at +3d and +4wks (P < 0.05). No age‐related differences were observed in mRNA expression of IGF‐1Ea, MGF, MyoD1 and HGF with retraining, whereas myostatin expression levels were more down‐regulated in YM compared to OM at +3d (P < 0.05). In conclusion, the diminished muscle re‐growth after immobilisation in elderly humans was associated with a lesser response in satellite cell proliferation in combination with an age‐specific regulation of myostatin. In contrast, expression of local growth factors did not seem to explain the age‐related difference in muscle mass recovery.